Insurgências em cinemas inventados : Era o Hotel Cambridge e Los silencios - Andrade, Rafael Beck (2021)
This research investigates the processes of reterritorialization and insurgencies of subjectivities through audiovisual invention, having as study objects the Brazilian feature films Era o Hotel Cambridge (Eliane Caffé, 2016) and Los silencios (Beatriz Seigner, 2017). From these films and from the theoretical excavation linked to territorial movements – a dear theme for the author -, the germination of territories, the insurgence of subjectivities, the actual processes of invention raised by these films are delirious: reterritorialization of individuals in the construction of subjectivities , insurrection of spheres in active micropolitical reactions of insurgency, creation of heterotopic places for the experience of dissident bodies, performatization of open wounds through marginal bodies, resumption of ancestral memory to make the present occupant/occupied body, decolonization of the desire created by the system colonial-capitalistic.